Clinical Outcomes of Upfront Stereotactic Radiosurgery Alone for Patients With 5 to 15 Brain Metastases. Issue 2 (6th July 2018) - Hughes, Ryan T; McTyre, Emory R; LeCompte, Michael; Cramer, Christina K; Munley, Michael T; Laxton, Adrian W; Tatter, Stephen B; Ruiz, Jimmy; Pasche, Boris; Watabe, Kounosuke; Chan, Michael D
Abstract: BACKGROUND: The role of primary stereotactic radiosurgery (SRS) for patients with >4 brain metastases (BM) remains controversial. OBJECTIVE: To compare the outcomes of patients treated with upfront SRS alone for 1, 2 to 4, and 5 to 15 BM and assess for predictors of clinical outcomes in the 5 to 15 BM group. METHODS: A total of 478 patients treated with upfront SRS were stratified by number of lesions: 220 had 1 BM, 190 had 2 to 4 BM, and 68 patients had 5 to 15 BM. Overall survival and whole brain radiotherapy-free survival were estimated using the Kaplan–Meier method. The cumulative incidences of local failure and distant brain failure (DBF) were estimated using competing risks methodology. Clinicopathologic and dosimetric parameters were evaluated as predictors of survival and DBF in patients with 5 to 15 BM using Cox proportional hazards. RESULTS: Median overall survival was 8.0, 6.3, and 4.7 mo for patients with 1, 2 to 4, and 5 to 15 BM, respectively ( P  = .14). One-year DBF was 27%, 44%, and 40%, respectively ( P  = .01). Salvage SRS and whole brain radiotherapy rates did not differ. Progressive extracranial disease and gastrointestinal primary were associated with poor survival while RCC primary was associated with increased risk of DBF. No evaluated dose-volume parameters predicted for death, neurologic death or toxicity. CONCLUSION: SRS for 5 to 15 BM is well tolerated without evidence of an associated increase in toxicity, treatment failure, or salvage therapy. Further prospective, randomized studies are warranted to clarify the role of SRS for these patients. Graphical Abstract: